Serum levels of VEGF-A, sVEGFR-2 and galectin-3 do not correlate with clinical stage, tumor size, or effectiveness of perioperative chemotherapy in patients with non-metastatic breast cancer - Iga Grochoła-Małecka; Paulina Czajka-Francuz; Aleksander Jerzy Owczarek; Jerzy Wojnar; Gabriela Handzlik; Tomasz Francuz; Jerzy Chudek (Annales Academiae Medicae Silesiensis, 2022)
Introduction Tumor angiogenesis is regulated by numerous cytokines and growth factors, with vascular endothelial growth factor (VEGF), soluble vascular endothelial growth factor receptor 2 (sVEGFR-2), and galectin-3, playing a significant role in the process. There are conflicting data concerning changes in serum VEGF, sVEGFR-2 and galectin-3 levels in breast cancer (BC) patients during the course of the disease and chemotherapy (CTH). This study aimed to assess the serum levels of VEGF-A, sVEGFR-2, and galectin-3 in women starting adjuvant and neoadjuvant therapy for BC, and their changes during the treatment.